Value Co-creation in Non-profit Accommodation Platforms - Medina-Hernandez, Vivian C.; Ferrer-Rosell, Berta; Marine-Roig, Estela (Frontiers in Psychology, 2021)
Value co-creation in the sharing accommodation sector has been extensively analyzed but mainly with Airbnb as a reference, and mostly focusing on guests’ perceptions. The aim of this study is to analyze the possible value co-created for users (guests and hosts) in the non-profit sharing accommodation platforms Couchsurfing and HomeExchange. This study also aims to analyze if the co-created value in these platforms is different from the co-created value in for-profit platforms, as well as how the outcomes, resources, and practices of the value co-creation process can help to create wellbeing for the individuals involved in the accommodation experience. Given that most of the existing literature on value co-creation in sharing accommodation platforms is based on Airbnb and on guest perspectives, this study is a pioneer in analyzing how guests and hosts co-create value in the context of non-profit accommodation platforms using online travel reviews from non-profit platforms, and how the co-created value contributes to the wellbeing of the individuals involved. Results show that a set of tangible and intangible resources, such as the home and its amenities, help users on non-profit platforms to co-create value, and that interaction and social practices between guests and hosts help to co-create value for each other. This implies that non-profit accommodation platforms may contribute more to their users’ social dimensions of wellbeing than for-profit platforms where the host is usually absent in the experience, such as Airbnb. This study also demonstrates that the co-created value in non-profit platforms depends on the modus operandi of each platform. On Couchsurfing, guests and hosts co-created more value from their social practices, and on HomeExchange, value co-creation depended more on tangible and intangible resources.